Broadening of Distribution of Trap States in PbS Quantum Dot Field-Effect Transistors with High‑k Dielectrics - Nugraha, Mohamad I; Häusermann, Roger; Watanabe, Shun; Matsui, Hiroyuki; Sytnyk, Mykhailo; Heiss, Wolfgang; Takeya, Jun; Loi, Maria A (ACS applied materials & interfaces, 2017)
We perform a quantitative analysis of the trap density of states (trap DOS) in PbS quantum dot field-effect transistors (QD-FETs), which utilize several polymer gate insulators with a wide range of dielectric constants. With increasing gate dielectric constant, we observe increasing trap DOS close to the lowest unoccupied molecular orbital (LUMO) of the QDs. In addition, this increase is also consistently followed by broadening of the trap DOS. We rationalize that the increase and broadening of the spectral trap distribution originate from dipolar disorder as well as polaronic interactions, which are appearing at strong dielectric polarization. Interestingly, the increased polaron-induced traps do not show any negative effect on the charge carrier mobility in our QD devices at the highest applied gate voltage, giving the possibility to fabricate efficient low-voltage QD devices without suppressing carrier transport.